The global burden of diabetes: prevalence, prevention and recommendations: La carga global de la diabetes: prevalencia, prevención y recomendaciones - Pérez, Miguel (2019)
The global burden of diabetes, a major cause of death, morbidity, and health care expenditures, now represents one of the greatest threats to global health and development. The main behavioral and biological determinants of diabetes are diets of processed sugars and fats, low physical activity levels, and overweight and obesity (Birn, Pillay, & Holtz, 2017). As one of the four major non-communicable diseases (NCDs), Diabetes Mellitus (DM) has attracted a great deal of attention from global health authorities. In fact, the World Health Organization has developed a strategy to address increasing rates of DM including prevention, management, access to essential medicines, and surveillance. A comprehensive approach integrating health care policy, health promotion, and health education is necessary for the prevention and subsequent treatment of diabetes around the world. DOI:10.25176/RFMH.v19.n2.2079